Business co-creation for service innovation in the hospitality and tourism industry. Issue 6 (12th June 2017) - Chen, Ja-Shen; Kerr, Don; Chou, Cindy Yunhsin; Ang, Chinhui
Abstract : Purpose: This study aims to test a theoretical model of co-creation dynamics, service innovation and competitive advantage. The authors explore the dynamics of collaboration between travel agents and their suppliers in co-creating value for their customers. A research model is proposed to examine the relationship among six co-creation elements (co-creation dynamics), service innovation, competitive advantage and two antecedents: technology adoption and environmental change and the moderating effects of trust. Design/methodology/approach: An empirical survey was performed based on travel agencies in Taiwan and Malaysia. A total of 105 valid responses from Taiwan and 102 valid responses from Malaysia were received. SPSS and partial least square were used to analyze the data. Findings: A new six-element construct of co-creation dynamics was suggested. All the proposed effects were found significant in which trust enhanced the effect of elements of innovation for Taiwan travel agencies. However, in contrast to the proposed hypotheses, technology adoption had no direct effect, whereas trust had no moderating effect for Malaysia travel agencies. Practical implications: This study suggests that managers should include co-creation approaches with partners and customers while developing new services. The identification of areas that may be lacking can allow managers to develop capabilities to improve business co-creation competency. Originality/value: This study links the relational view with service-dominant logic that emphasizes business co-creation and service innovation as operant resources and a key fundamental source for competitive advantage. This study also looks at interpreting business co-creation and discusses whether business co-creation affects service innovation in the hospitality and tourism industry.